Metacognitive Reading Strategy Direct Instruction Effects on Students' Metacognitive Reading Strategy Awareness and Their Perceptions of Metacognitive Reading Strategy Instruction at Guder Secondary School Grade 11 in Oromia, Ethiopia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study examined the effects of metacognitive reading strategy explicit instruction on Grade 11 students’ metacognitive reading strategy awareness and perceptions about the strategy direct instruction. Metacognitive Reading strategy Awareness Inventory and interview were used as data gathering instruments. In order to achieve these objectives, a quasi-experimental research design was employed. Students in experimental group participated in the direct instruction of metacognitive reading strategy whereas control group participated in learning of metacognitive reading the strategy in a conventional way. An ANCOVA was used to analyze data after pretest and posttest in order to test the hypothesis of the study. It is found that metacognitive reading strategy direct instruction affected Grade 11 students' metacognitive reading strategy awareness. The mean scores of the experimental group increased significantly from M=2.77, SD=.20 (pretest) to M=4.29, SD=.13 (posttest). Among the three elements of metacognitive awareness of reading strategy inventory, supportive reading strategy was the least affected by the instruction (M=3.85). To the contrary, problem solving reading strategy (M=4.00) was mostly affected by the instruction. Global reading strategy (M= 3.89) was moderately affected by the instruction. In conclusion, interview result indicated that interviewees had good perception about the direct instruction of metacognitive reading strategy